The Scottish Feminist Judgments Project - Sharon Cowan (Oñati Socio-Legal Series)
This article lays out the inner workings of the new Scottish Feminist Judgments Project (SFJP). Against the backdrop of our discussions at the FJPs meeting in Onati, it discusses the ways in the which the SJP has evolved, including the methodological and theoretical choices that have shaped the project so far. The SFJP is part of a collective and collaborative endeavour that forms part of a critical mass strategy for change. It also offers its own unique insights into the ways that issues such as national identity, as well as gender, can influence the extent to which feminist voices can challenge the legal cultures and traditions in a particular jurisdiction. Although FJPs are only one way of challenging legal orthodoxy, they offer an opportunity for wide scale collective activism and critique across different legal jurisdictions and cultures that could help to bring legal cultural change.